2014
DOI: 10.1152/ajpendo.00272.2014
|View full text |Cite
|
Sign up to set email alerts
|

Leptin restores the insulinotropic effect of exenatide in a mouse model of type 2 diabetes with increased adiposity induced by streptozotocin and high-fat diet

Abstract: restores the insulinotropic effect of exenatide in a mouse model of type 2 diabetes with increased adiposity induced by streptozotocin and high-fat diet. Am J Physiol Endocrinol Metab 307: E712-E719, 2014. First published August 26, 2014; doi:10.1152/ajpendo.00272.2014.-Leptin may reduce pancreatic lipid deposition, which increases with progression of obesity and can impair ␤-cell function. The insulinotropic effect of glucagon-like peptide-1 (GLP-1) and the efficacy of GLP-1 receptor agonist are reduced assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Despite immensely high leptin levels, there was only a trend towards an improvement in blood glucose levels and oral glucose tolerance. Other studies have reported that leptin therapy in HFD/STZ mice caused a partial improvement in blood glucose and glucose tolerance [44] , [45] . Discrepancies between these studies and ours may be due to differences in the timing of STZ relative to HFD treatment, the dose of STZ, the % of fat in the diet, or the method of leptin delivery [44] , [45] .…”
Section: Discussionmentioning
confidence: 97%
“…Despite immensely high leptin levels, there was only a trend towards an improvement in blood glucose levels and oral glucose tolerance. Other studies have reported that leptin therapy in HFD/STZ mice caused a partial improvement in blood glucose and glucose tolerance [44] , [45] . Discrepancies between these studies and ours may be due to differences in the timing of STZ relative to HFD treatment, the dose of STZ, the % of fat in the diet, or the method of leptin delivery [44] , [45] .…”
Section: Discussionmentioning
confidence: 97%
“…This mouse model has commonly been referred to as a model for type 2 diabetes. However, most studies have shown that these mice are not hyperinsulinemic but are glucose intolerant (Lv et al ., ; Xue et al ., ; Fu et al ., ; Mali et al ., ; Sakai et al ., ; Wang et al ., ) .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic blockade of AT1 with telmisartan improved glucose tolerance and other symptoms of the metabolic syndrome via improved leptin signalling and sensitivity associated with amelioration of the hyperleptinaemia, suggesting that the improvements in fasting plasma glucose in the present study were derived from similar mechanisms. In the STZ‐induced diabetic mouse, exogenous leptin restored the insulinotropic effect of exenatide, suggesting that elevated leptin facilitates GLP‐1‐mediated effects on insulin signalling. In the present study, OLETF presented with the characteristic hyperleptinaemia, which is partially ameliorated with ARB and combination treatments.…”
Section: Discussionmentioning
confidence: 95%